Two new species of Exallonyx Kieffer (Hymenoptera: Proctotrupidae) from China, with a key to the Chinese species - Liu, Jingxian; He, Junhua; Xu, Zaifu (Zootaxa, 2006)
Two new species, Exallonyx strictus and Exallonyx pingbianensis, are described and illustrated herein from China. Both species belong to the formicarius-group of subgenus Exallonyx Kieffer. A key for the Chinese formicarius-group is given.